Inter-brain ERPs alignment during a joint Simon task: An EEG hyperscanning study - Francesca Miti; Jlenia Toppi; Angela Ciaramidaro; Laura Astolfi; Cristina Iani; Sandro Rubichi (PLoS ONE, 2026)
The joint Simon task (JST) is widely employed to study the neurocognitive mechanisms underlying joint actions. Behavioral and electrophysiological research using this task suggests that individuals integrate their partners’ actions into their cognitive representations during collaborative activity, a concept referred to as the co-representation hypothesis. A key open question is whether this co-representation is accompanied by inter-brain synchronization. In this study, we investigated inter-brain dynamics in pairs of interacting participants by recording scalp electrophysiological (EEG) activity from 88 individuals performing the JST in dyads, using an EEG hyperscanning setup. We calculated the EEG-JSE, which represents the difference in ERP peak latencies between corresponding and non-corresponding trials, as an index of the neural joint Simon effect. This analysis focused on two ERP components, N2 and P3, which have been associated with the inhibition of response preparation and execution, respectively—processes that are crucial to joint Simon task performance. Furthermore, we examined whether the EEG-JSEs of the two participants in each pair were synchronized. Our findings revealed temporal alignment between the responding and non-responding participants in the pair, highlighting the unique inter-brain interaction dynamics that arise from the demands of performing a task jointly.